2015
DOI: 10.1590/0034-737x201562010006
|View full text |Cite
|
Sign up to set email alerts
|

Controle da ferrugem e da broca-dos-ramos da figueira com diferentes fungicidas e inseticidas

Abstract: Temperaturas e precipitações elevadas favorecem a incidência da ferrugem (Cerotelium fici(Cast.)) e da broca-dos-ramos (Azochis gripusalis (Walker, 1859) (Lepidoptera: Pyralidae)), limitando a produção comercial de figos. O objetivo deste trabalho foi comparar a eficiência de fungicidas e inseticidas alternativos em relação à de produtos convencionais registrados para a cultura. Foram realizados dois experimentos, no delineamento de blocos inteiramente casualizados, com quatro repetições, no setor de fruticult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Thus, to efficiently improve fig trees for cultivation in tropical climates, resistance to rust and the direct and indirect effects of this disease on production must be taken into account. However, studies targeting diseases are difficult to conduct; therefore, indirect assessment via productivity is the best approach, since more resistant plants tend to be more productive (Mezzalira, Piva, Nava, Paulus, & Santin, 2015). The genetic variation coefficient (deviation from the genetic standard), expressed as a percentage of the mean, is an indicator of the relative magnitude of changes in a trait through selection during a breeding program (Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to efficiently improve fig trees for cultivation in tropical climates, resistance to rust and the direct and indirect effects of this disease on production must be taken into account. However, studies targeting diseases are difficult to conduct; therefore, indirect assessment via productivity is the best approach, since more resistant plants tend to be more productive (Mezzalira, Piva, Nava, Paulus, & Santin, 2015). The genetic variation coefficient (deviation from the genetic standard), expressed as a percentage of the mean, is an indicator of the relative magnitude of changes in a trait through selection during a breeding program (Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the low effectiveness of Bordeaux mixture and lime sulfur mixture in controlling anthracnose in passion fruit under the environmental conditions in which the experiment was carried out, Ming et al (2012) reported the control of leaf diseases of sweet passion fruit in organic farming with lime sulfur mixture at 0.5% of concentration and Mezzalira et al (2015) reported the fig rust control with Bordeaux mixture at 1.5%. Ferreira et al (2015) evaluated the effect of organic waste as an alternative measure to control fusarium in yellow passion fruit, and babaçu coconut waste at a concentration of 60 g kg -1…”
Section: Resultsmentioning
confidence: 99%
“…Ainda no século XIX se propunha a inserção de cordões de árvores em meio aos cafezais, seguindo a linha de nível, como estratégia para conter o transporte de terra pela enxurrada e o consequente assoreamento e obstrução dos rios. Por volta de 1930, começam a ser empregadas em maior escala as chamadas "curvas de nível" e os terraços agrícolas, como medidas para diminuir o efeito das enxurradas (FONSECA FILHO, 1934;MENDES, 1936MENDES, , 1938CARDOSO, 1939aCARDOSO, , 1939bABRAMIDES NETO;BORGONOVI, 1941;SOUZA, 1942;RESENDE, 1943;MARQUES, 1943).…”
Section: Aspectos Técnicos E Ambientais Da Conservação Do Solo No Brasilunclassified